Validitas Perangkat Pembelajaran Matematika Berbasis Problem Based Learning (PBL) Pada Materi Arimatika Sosial Kelas VII - anjani wira murti; leo adhar effendi; nofri yandi; zetrius lita (Universitas Muhammadiyah Semarang, 2021)
This study aims to produce mathematics learning tools in the form Learning Implementation Plans (RPP) and Student Worksheets (LKPD) using a Problem Based Learning (PBL) mathematics learning model on social arithmetic material for class VII tested valid. Development of learning tools in this study uses the method R&D development using the modified ADDIE model into 3 stages, namely: 1) Analysis, 2) Design, 3) Development. In the ADDIE model, the researcher does not use the Implementation stage and the Evaluation stage because at the moment it is still in the atmosphere of the Covid-19 pandemic. The data collections instruments in this study were the RPP validation sheets, and the LKPD validation sheet. The data collection technique used is validation data from 2 Mathematics Education Lecturers FKIP UIR and 2 Mathematics Teachers at MTs Al-Multazam Kerubung Jaya. The analytical techniqueused is validation data analysis. From the results of the study, the result of the RPP validation were 86,83% with a very valid validation level category and 81,54% LKPD validation results with a fairly valid validation level category. Based on the results of these studies, it can be concluded that the development of mathematics learning tools baseb on Problem Based Learning (PBL) in the sevent grade social arithmetic material has been tested for validity.